Some New Hermite–Hadamard-Type Inequalities Associated with Conformable Fractional Integrals and Their Applications - Arshad Iqbal; Muhammad Adil Khan; Sana Ullah; Yu-Ming Chu (Journal of Function Spaces)
In this article, we establish some new Hermite–Hadamard-type inequalities involving the conformable fractional integrals. As applications, several inequalities for the approximation error in the midpoint formula and certain bivariate means are derived.